2013
DOI: 10.1038/nprot.2013.080
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop optogenetic intervention in mice

Abstract: Optogenetic interventions offer novel ways of probing, in a temporally specific manner, the roles of specific cell types in neuronal network functions of awake, behaving animals. Despite the unique potential for temporally specific optogenetic interventions in disease states, a major hurdle in its broad application to unpredictable brain states in a laboratory setting is constructing a real-time responsive system. We recently created a closed-loop system for stopping spontaneous seizures in chronically epilept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
135
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 48 publications
0
135
0
Order By: Relevance
“…An on-demand intervention approach, in which intervention is delivered in a responsive fashion only at the time of seizures, requires fast, on-line seizure detection. A flexible system for on-line seizure detection, in which the experimenter can select from a variety of algorithms and tune the detector to the specific EEG signature of a given animal has been developed and made widely available 17 . However, the appearance of seizures on EEG (or any recording modality) can vary substantially between individual animals, even within the same model, and certainly across different types of epilepsy.…”
Section: Specificity Is Key To Unlocking Icto- and Epileptogenesismentioning
confidence: 99%
“…An on-demand intervention approach, in which intervention is delivered in a responsive fashion only at the time of seizures, requires fast, on-line seizure detection. A flexible system for on-line seizure detection, in which the experimenter can select from a variety of algorithms and tune the detector to the specific EEG signature of a given animal has been developed and made widely available 17 . However, the appearance of seizures on EEG (or any recording modality) can vary substantially between individual animals, even within the same model, and certainly across different types of epilepsy.…”
Section: Specificity Is Key To Unlocking Icto- and Epileptogenesismentioning
confidence: 99%
“…Furthermore, the repertoire of optogenetic tools is ever expanding to include opsins with altered ion specificity and increased effectiveness (Berndt et al 2014;Chuong et al 2014), and this technology is being used to research possible treatments for a multitude of neurological disorders, including epilepsy, Parkinson's disease, and Alzheimer's disease (Gradinaru et al 2009;Krook-Magnuson and Soltesz 2015;Yamamoto et al 2015). By using optogenetics to control the activity of specific circuits, important discoveries have been made regarding the circuits involved in epileptiform activity in in vitro and in vivo seizure or epilepsy models (Tønnesen et al 2009;Kokaia 2011;Wykes et al 2012;Armstrong et al 2013;Krook-Magnuson et al 2013Paz et al 2013;Rossignol et al 2013;Sukhotinsky et al 2013;Berglind et al 2014;Ledri et al 2014). Soon after early experiments showing optogenetic control of seizure-like events in hippocampal culture preparations (Tønnesen et al 2009), several in vivo studies showed that optogenetics can be used to manipulate specific neuronal circuits within rodent models of epilepsy to control seizures (Wykes et al 2012;Armstrong et al 2013;Krook-Magnuson et al 2013Paz et al 2013).…”
Section: Optogenetic Targeting Of Specific Circuits In Epilepsy Applimentioning
confidence: 99%
“…By using optogenetics to control the activity of specific circuits, important discoveries have been made regarding the circuits involved in epileptiform activity in in vitro and in vivo seizure or epilepsy models (Tønnesen et al 2009;Kokaia 2011;Wykes et al 2012;Armstrong et al 2013;Krook-Magnuson et al 2013Paz et al 2013;Rossignol et al 2013;Sukhotinsky et al 2013;Berglind et al 2014;Ledri et al 2014). Soon after early experiments showing optogenetic control of seizure-like events in hippocampal culture preparations (Tønnesen et al 2009), several in vivo studies showed that optogenetics can be used to manipulate specific neuronal circuits within rodent models of epilepsy to control seizures (Wykes et al 2012;Armstrong et al 2013;Krook-Magnuson et al 2013Paz et al 2013). Their success in stopping or delaying seizure progression by using optogenetics to inhibit a small percentage of principal cells indicated the potential for optogenetics as a promising therapeutic in epilepsy.…”
Section: Optogenetic Targeting Of Specific Circuits In Epilepsy Applimentioning
confidence: 99%
“…This is an important control feature in attenuating neurobiological diseases in animal models, such as epilepsy, because they can be turned on as soon as seizure-like waveforms are detected. [63][64][65] However, one drawback that can arise with such multielectrode arrays is that multiple deep penetration points can cause brain injury during insertion, especially when trying to stimulate and record from deeper brain regions. Each recording electrode in the array can be hundreds of micrometers in diameter, and each causes neuronal damage as the array is driven into the brain.…”
Section: Tethered Systemsmentioning
confidence: 99%